Second Language Writing Anxiety among Faculty Scholars of a State University in the Philippines and Its Sex-Disaggregated Data - Mercedita M. Reyes; Sharina Carla S. Merculio; Joan C. Ravago (Qubahan Academic Journal)
The study investigated the causes and the nature of writing anxiety specifically in the use of English as the second official language of the Philippines. Further, it accounted and analyzed its sex-disaggregated data. This was done among faculty scholars of Central Luzon State University. The respondents were randomly chosen from among the purposively identified faculty scholars of the university pursuing their graduate degrees - master’s and doctorate, in the different graduate curricular offerings in various universities in the Philippines and abroad, that require a thesis or dissertation as the final requirement for obtaining a graduate degree.  The Second Language Writing Anxiety Inventory (SLWAI) of Cheng (2004), a questionnaire composed of 22 items with three open-ended questions was used to collect responses. The responses were scored and measured on a five-point Likert response scale. The differences in Second Language Writing Anxiety (SLWA) between male and female participants were analyzed using the Mann-Whitney Test, which is ideal for analyzing statistically the difference between the distributions of data of unparalleled groups with the comparison of ranks and scores. Based on the study findings, the most prominent nature of SLWA among participants is cognitive anxiety. Other sources of anxiety include the availability of external and internal resources and environmental elements. In relation to sex, males scored higher in terms of the level of anxiety compared to females. Lastly, it is forwarded that educators and the pedagogical approach may utilize a positive feedback mechanism as negative evaluation promotes anxiety even in composing in a second language.